Toward Father‐friendly Parenting Interventions: A Qualitative Study. Issue 2 (9th June 2018) - Sicouri, Gemma; Tully, Lucy; Collins, Daniel; Burn, Matthew; Sargeant, Kristina; Frick, Paul; Anderson, Vicki; Hawes, David; Kimonis, Eva; Moul, Caroline; Lenroot, Roshel; Dadds, Mark
Abstract : Levels of father participation in parenting interventions are often very low, yet little is known about the factors which influence father engagement. We aimed to qualitatively explore perceived barriers to, and preferences for, parenting interventions in a community sample of fathers. Forty‐one fathers across nine focus groups were interviewed using a semi‐structured interview. Data were analysed using inductive thematic analysis. Key barriers to father participation identified included: the perception that interventions are mother‐focused; beliefs about gender roles regarding parenting and help‐seeking; mothers' role as 'gatekeeper'; lack of knowledge and awareness of parenting interventions; and lack of relevance of interventions. Fathers reported preferences for specific content and intervention features, facilitator characteristics, practical factors, and highlighted the need for father‐targeted recruitment and advertising. Many of the barriers and preferences identified are consistent with previous research; however, fathers' beliefs and attitudes around gender roles and help‐seeking, as well as the perception that interventions are predominantly mother‐focused, may be key barriers for community fathers. Strategies to overcome these barriers and better meet the needs of fathers in promoting and delivering parenting interventions are discussed.